تصميم وتنفيذ منصة تجريبية لقياس الكفاءة واألداء الديناميكي لمحركات BLDC الكهربائية (Comprehensive Journal of Science, 2025)
Brushless electric motors are considered the optimal and preferred choice for designing andbuilding unmanned aerial vehicles (UAVs). This is due to the fact that these motors do not containbrushes like traditional DC electric motors, witch reduces friction and consequently increasesoperational efficiency and extends the motor`s lifespan. In this paper, a tool was designed tomeasure the performance of the brushless electric motor using a network of sensors that monitorcurrent, voltage and rotational speed. The system also measures airspeed and send these readings toArdunio Uno control unit, which stores and analyzes the data to determine the motor`s performanceunder various operating conditions.The platform includes a LCD screen to show the measured indicators in real time, as well as storageunit to save the data for future analysis. The platform was designed to be user-friendly and flexible,allowing both maintenance or and developers to utilize the data for routine maintenance or toenhance motor performance
Keywords: electric motor, control, arduino, platform, measurement